Does age modify the association between psychosocial factors at work and deterioration of self-rated health? - Burr, Hermann; Hasselhorn, Hans Martin; Kersten, Norbert; Pohrt, Anne; Rugulies, Reiner (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVES ': 'Few epidemiological studies have examined whether associations of psychosocial working conditions with risk of poor health differ by age. Based on results from mostly cross-sectional studies, we test whether (i) psychosocial relational factors (social support) are more strongly associated with declining health of older than younger employees and (ii) psychosocial job factors (workpace, influence, possibilities for development) are more strongly associated with declining health of younger than older employees. ' ' METHODS ': 'We extracted two cohorts from the Danish Work Environment Cohort Study (DWECS): the 2000–2005 and 2005–2010 cohorts. The participating 5281 employees with good self-rated health (SRH) at baseline were observed in 6585 5-year time windows. Using log-binomial regression analyses, we analysed whether psychosocial factors at work predicted 5-year deterioration of SRH. Effect modification by age was estimated by calculating relative excess risk due to interaction (RERI). ' ' RESULTS ': 'High workpace among men, low influence at work as well as low social support from colleagues among women, and low possibilities for development and low social support from supervisors among both genders predicted 5-year decline in SRH. Of the 20 interaction analyses, only 1 was statistically significant and in the opposite direction of what was hypothesized (higher risk for declining SRH among middle-aged men with low possibilities for development compared to the young men with high possibilities for development). ' ' CONCLUSIONS ': 'Psychosocial working conditions predicted decline in SRH in this 5-year follow-up study. The model did not support our hypotheses about modifying effects by age.
Keywords: age; ageing; COPSOQ; decision authority; DWECS; interaction; job factor; older worker; psychosocial; psychosocial factor; psychosocial work environment; relational factor; self-rated health; skill discretion; work